Applying UML and patterns : an introduction to object-oriented analysis and design and iterative development. - Larman, Craig, ....- (Upper Saddle River, NJ : Prentice Hall, 2005)
This third edition again delivers a clear path for students and professionals to learn and apply object-oriented analysis and design. The first two editions of this book have achieved gross sales of more than 60,000 units through the domestic retail channel Timely and up-to-date; compliant with UML 2.0 and the latest trends in design patterns and object-oriented analysis and design More gold from one of the leading names in software engineering- Craig Larman! The mastery of object-oriented analysis and design (OOA/D) principles and concepts is critical for anyone seeking to create robust and maintainable object systems. This third edition presents a well-defined roadmap, so the reader can move along a step-by-step process from requirements gathering all the way to code generation. The author teaches the skill of OOA/D using the latest version of the industry standard modeling language (UML 2.0). He also allows the reader to learn and apply the popular concept of design patterns, and therefore helps readers accelerate their mastery of analysis and design. The author retains his thorough treatment of a single case study to help readers gain a big picture of successful software development. Once again, this book delivers, and furthers Craig Larman's name among software engineering luminaries.
Keywords: Object-georiënteerd programmeren